Tingkat Kekhawatiran Gen Z atas Keuangan Pensiun Orang Tua dan Strategi Kebebasan Finansial - Syarifudin Yuus (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Descriptive research involving 75 Gen Z on Gen Z's concerns about their parents' economic and financial conditions in retirement concluded that 86.7 percent of Gen Z were worried about their parents' economic and financial conditions in retirement, while 13.3 percent of Gen Z were not worried. As many as 66.7 percent of Gen Z were not sure that their parents would be financially free in old age, while 33.3 percent of Gen Z were sure that their parents would be prosperous in retirement. The implication is that if Gen Z is already working and is forced to help their parents' economy, then 53.3 percent of Gen Z are willing to help their parents' retirement by 10% of their salary. This means that 1 in 2 Gen Z are only willing to set aside 10% of their salary to help their parents in retirement. As a solution to Gen Z's concerns about their parents' economic conditions during retirement, ways to overcome this include: 1) the need to have sufficient retirement savings, 2) maintaining health so that it does not decline during retirement, 3) avoiding a consumptive lifestyle, 4) not depending on their children, and 5) avoiding the occurrence of a sandwich generation.